Pelatihan Pengenalan Literasi Digital Bagi Siswa SMP Negeri 7 Langsa - Chairuddin, Chairuddin; Asra, Surya; Rahman, Aulia; Wibowo, Guntur Arie (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
The level of digital literacy of the Indonesian people is still low, including young generation. Therefore, students must be prepared early on digital literacy. This activity aims to provide knowledge in the form of skills for junior high school students to be able to recognize and utilize information technology, especially students' digital literacy skills. This activity was in the form of training on the introduction of basic digital literacy. As a result, several mixed approaches are used, namely lecturing, discussion, and practice. The materials taught in this training include digital culture, online security skills, digital ethics, creating emails and finding and storing information for learning. From the FGDs conducted on teachers and students, it revealed that after participating in this training there was a change in students' attitudes in learning towards online learning. Students who have attended the training can recognize digital literacy and begin to use digital information and electronic books as learning resources, especially when doing assignments and homework. Therefore, it can be said that this training has made a positive contribution to increasing students' understanding of digital literacy.